Launching Global Journal of Medical and Clinical Case Reports - Muhammed Mubarak; Javed I. Kazi (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2014)
During the recent past, the biomedical publishing field has witnessed a decline in the publishing of the case reports by many journals. This trend is not particularly helpful for the medical community at large. The main reason for the above trend is the low citation value of the case reports, which reduces the overall impact factor of the journals. This competition of the journals for journal ranking by the yardstick of impact factor has resulted in many major journals abandoning the due share of space to the case reports. In fact, some reputable journals have even decided not to accept case reports anymore or they have made the criteria of accepting the case reports so strict that no case report finds space there [1-3].